1982
DOI: 10.1177/009579848200800202
|View full text |Cite
|
Sign up to set email alerts
|

Racial Group Concept and Self-Esteem in Black Children

Abstract: The relationship of racial group concepts (racial preference and racial attitudes) to general and specific self-esteem in Black children was examined. The study also attempted to validate the belief of Nobles (1973) that racial group attitudes influence the Black American's concept of "self." The subjects were 210 Black children in grades three to six. A Black experimenter administered a variation of the Coopersmith Self-Esteem Inventory to measure general and specific self-esteem, and a measure designed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
4
9
0
Order By: Relevance
“…This finding was supported by the significant difference between the two constructs, and supports the findings of Katz et al (1975) and M.L. Clark (1982). In the context of the present study, at least, it was not necessary to sacrifice a positive ingroup identity to achieve a positive selfconcept (and vice versa), as seemed to occur with Corenblum and Annis' (1993) participants.…”
Section: Preference and Self-conceptsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding was supported by the significant difference between the two constructs, and supports the findings of Katz et al (1975) and M.L. Clark (1982). In the context of the present study, at least, it was not necessary to sacrifice a positive ingroup identity to achieve a positive selfconcept (and vice versa), as seemed to occur with Corenblum and Annis' (1993) participants.…”
Section: Preference and Self-conceptsupporting
confidence: 88%
“…M.L. Clark (1982) found no relationship between ingroup preference and self-esteem, while Hughes and Demo (1989) found a positive relationship between racialesteem and self-esteem. One study with native Canadian children found a negative relationship between ingroup preference and self-esteem (Corenblum & Annis.…”
Section: Relationship Between Ingroup Preference and Self-conceptmentioning
confidence: 87%
See 1 more Smart Citation
“…In general, Black male youths demonstrate higher levels of self-esteem than their Anglo American cohorts-in many ways, social scientists have been so perplexed by this phenomenon to the point that there is a continued effort to find some pathological cause for high self-esteem levels in black youth (Clark, 1992;Whaley, 1993). For example, Osborne (1995Osborne ( , 1997 refers to high levels of perceived self-esteem in black males who have low academic achievement as the "disidentification" hypothesis.…”
Section: Self-esteem and African American Youthmentioning
confidence: 99%
“…In the school setting, African American youth are underrepresented in gifted education programs (Bonner, 2000). In fact, a great deal of education research literature has focused on the perceived social inadequacies of black youth in comparison to their Anglo American cohorts on differences in scholastic achievement, identity development, and levels of self-esteem (Clark, 1992). Studies in these areas tend to describe black youth as less intelligent, bicultural in self-concept, and less confident about their ability to achieve.…”
Section: Introductionmentioning
confidence: 99%